Paul Rudolph: portrayed architectures in Florida’s landscape - Galván Desvaux, Noelia; Álvaro-Tordesillas, Antonio; Jiménez Jiménez, Marina (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
The American house from the late 40s leaded the architecture of that period since it became shelter for human life after the war. With that in mind, and based on the teachings of Wright and the migrating European masters, many architects proposed a flexible domestic space open to their environment, where they could rediscover contact with the landscape. It was a matter of placing the house back in relation to the land, or at least that is how Paul Rudolph perceived it in the houses he designed for Florida, a setting that was starting to become established as a holiday destination for the average American. Rudolph understood the environment as one more element of his work, and so his drawings show. The analysis of his graphics reveals a series of elements that highlight the space where the architecture lays, in an attempt to retrieve the poetic dimension of the landscape.
Keywords: Paul Rudolph; domestic architecture; landscape; drawing